2021
DOI: 10.1364/prj.433024
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface doublet-integrated bidirectional grating antenna enabling enhanced wavelength-tuned beam steering

Abstract: We propose and demonstrate an optical phased-array-based bidirectional grating antenna (BDGA) in silicon nitride waveguides. The BDGA is integrated with a miniaturized all-dielectric metasurface doublet (MD) formed on a glass substrate. The BDGA device, which takes advantage of alternately feeding light to its ports in opposite directions, is presumed to effectively provide a doubled wavelength-tuned steering efficiency compared to its unidirectional counterpart. The MD, which is based on vertically cascaded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Dynamic control of the beam wavefront is one of the grand challenges faced by traditional optical systems for various applications, such as adaptive optics, LiDAR, display, communication, etc . , Tunable metasurfaces have been viewed as a promising solution to achieve full control over the characteristics of the light.…”
Section: Applicationsmentioning
confidence: 99%
“…Dynamic control of the beam wavefront is one of the grand challenges faced by traditional optical systems for various applications, such as adaptive optics, LiDAR, display, communication, etc . , Tunable metasurfaces have been viewed as a promising solution to achieve full control over the characteristics of the light.…”
Section: Applicationsmentioning
confidence: 99%
“…SiN also suffers from less nonlinear losses with respect to Si [61], which allows waveguide Another method is to enlarge the FOV of PIC-OPA assisted by metasurfaces (named meta-assisted PIC-OPA). As shown in Figure 6b, the metasurface performs like an ultra-thin lens, which can enlarge the beam steering angle θ by M times [47][48][49]. Lee et al proposed and demonstrated a bidirectional grating antenna PIC-OPA integrated with a miniaturized all-dielectric metasurface doublet formed on a glass substrate atop the antenna array.…”
Section: Pic-opamentioning
confidence: 99%
“…The steering efficiency was confirmed to be boosted by a factor of ~3.1. The steering angle was up to 30 • with the wavelength from 1530 to 1595 nm [49]. However, for normal meta-OPA, the phase modulation is often generally accompanied by intensity modulation [42,44], which affects the side mode suppression ratio.…”
Section: Pic-opamentioning
confidence: 99%
“…OPAs exploit power splitters, phase shifters, and emitters to emit and steer the beam. The emitter configuration governs the nature of the beam emission, such as end-fire emission 6 , 7 or out-of-plane emission 8 , 9 . Current OPA developments are towards out-of-plane emission for the two-dimensional (2D) raster scanning of a point beam covering the field-of-view (FOV) of concern by tuning the laser wavelength and phase distribution across emitter channels 1 , 3 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The emitter configuration governs the nature of the beam emission, such as end-fire emission 6 , 7 or out-of-plane emission 8 , 9 . Current OPA developments are towards out-of-plane emission for the two-dimensional (2D) raster scanning of a point beam covering the field-of-view (FOV) of concern by tuning the laser wavelength and phase distribution across emitter channels 1 , 3 , 8 , 9 . Typically, OPAs incorporate diffractive-grating-based emitters to enable longitudinal beam scanning by tuning the wavelength of the input light.…”
Section: Introductionmentioning
confidence: 99%